Association between self-reported signs and symptoms and SARS-CoV-2 antibody detection in UK key workers. Issue 5 (May 2021) - Mulchandani, Ranya; Taylor-Philips, Sian; Jones, Hayley E.; Ades, A.E.; Borrow, Ray; Linley, Ezra; Kirwan, Peter D; Stewart, Richard; Moore, Philippa; Boyes, John; Hormis, Anil; Todd, Neil; et al.
Highlights: Roche ELECSYS and EUROIMMUN immunoassays were >93% sensitive in key workers. About one quarter of keyworkers without a previous positive PCR test believed they had COVID-19. However, of these, only 30% had serological evidence of COVID-19. Symptom profiles and timings suggest symptomatic seronegative individuals had non-COVID illnesses. Self-reported symptoms are not reliable in ascertaining past COVID-19 disease. Abstract: Background: Screening for SARS-CoV-2 antibodies is under way in some key worker groups; how this adds to self-reported COVID-19 illness is unclear. In this study, we investigate the association between self-reported belief of COVID-19 illness and seropositivity. Methods: Cross-sectional study of three key worker streams comprising (A) Police and Fire & Rescue (2 sites) (B) healthcare workers (1 site) and (C) healthcare workers with previously positive PCR result (5 sites). We collected self-reported signs and symptoms of COVID-19 and compared this with serology results from two SARS-CoV-2 immunoassays (Roche Elecsys® and EUROIMMUN). Results: Between 01 and 26 June, we recruited 2847 individuals (Stream A: 1, 247, Stream B: 1, 546 and Stream C: 154). Amongst those without previous positive PCR tests, 687/2, 579 (26%) reported belief they had COVID-19, having experienced compatible symptoms; however, only 208 (30.3%) of these were seropositive on both immunoassays. Both immunoassays had high sensitivities relative to previous PCR positivity (>93%); there was also limited decline in antibody titres up to 110 days post symptom onset. Symptomatic but seronegative individuals had differing symptom profiles and shorter illnesses than seropositive individuals. Conclusion: Non-COVID-19 respiratory illness may have been mistaken for COVID-19 during the outbreak; laboratory testing is more specific than self-reported key worker beliefs in ascertaining past COVID-19 disease.